2019
DOI: 10.1111/jace.16894
|View full text |Cite
|
Sign up to set email alerts
|

Indentation cracking and deformation mechanism of sodium aluminoborosilicate glasses

Abstract: Developing less brittle oxide glasses is a grand challenge in the field of glass science and technology, as it would pave the way toward new glass applications and limit the overall raw material usage and energy consumption. However, in order to achieve this goal, more insight into the correlation between the chemical composition and material properties is required. In this work, we focus on the mechanical properties of quaternary sodium aluminoborosilicate glasses, wherein systematic changes in glass chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
(146 reference statements)
1
13
0
Order By: Relevance
“…Hence, the enhanced crack resistance of the 4 mol% Al 2 O 3 glass cannot be attributed to densification. This observation is in agreement with a recent study on alumino borosilicate glasses by Januchta et al (2019a), who neither found a direct correlation between the fracture initiation resistance and densification. The significant changes in the fraction of boroxol and borate rings upon indentation rather indicate that those units have played a significant role during deformation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, the enhanced crack resistance of the 4 mol% Al 2 O 3 glass cannot be attributed to densification. This observation is in agreement with a recent study on alumino borosilicate glasses by Januchta et al (2019a), who neither found a direct correlation between the fracture initiation resistance and densification. The significant changes in the fraction of boroxol and borate rings upon indentation rather indicate that those units have played a significant role during deformation.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, it is worth noting that an enhanced fracture initiation load does not correspond to a higher fracture toughness, which describes the critical stress intensity factor for crack growth (Rouxel and Yoshida, 2017;Januchta et al, 2019a). Concerning the fracture toughness, it is even disadvantageous if the crack can surpass certain structural units (e.g., boroxol rings) and has to break less bonds on its way through the material (Januchta et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crack resistance is also depended on the bond strength (To et al, 2020), as the stronger the bonds in 9 For isotropic materials, the Bulk modulus K is related to the Young's modulus and Poisson's ratio as: the network, the more difficult to break. Januchta et al (2020) also correlate CR to the Bulk modulus 9 stating that flexible glasses can distribute the residual stress in a larger field. At this point, it should be elaborated that Hardness, which quantifies the resistance of a ceramic material to deformation and densification, is not inversely related to CR (Table 4).…”
mentioning
confidence: 79%
“…We then employ an approach that is similar to the method for recovery of indentation volume to estimate densification contribution to overall indentation deformation. 28,29 That is, we calculate the aging-induced side length recovery (L AR ) as, 𝐿 𝐴𝑅 = 𝐿 𝑠,𝑖 − 𝐿 𝑠,𝑎 𝐿 𝑠,𝑖 .…”
Section: Micro-indentation Experimentsmentioning
confidence: 99%